La gestion de la délinquance juvénile au Brésil et en France: convergences. - Frederico Couto Marinho; Joana Vargas (Sociétés et Jeunesses en Difficulté)
In the context of legislative changes, this paper compares the institutional responses to juveniles accused of a crime or offence in Brazil and in France. Research on juvenile justice, in the context of both countries, systematically highlights the major changes in the laws relating to juvenile delinquency which have occurred since the 1990s. For this reason we chose the cities of Belo Horizonte, Brazil, and Lille in France. To analyse the institutional responses to juvenile delinquency, taking into account legislative and regulatory changes, we relied on the evolution of police, justice and prison administration statistics in the two countries. The article shows that the legislative history of Brazil over the past twenty years has not been the same as that of France. However, the deep history of violence and human rights violations in Brazil, especially violence against children and adolescents, has led to the incomplete and inadequate adoption of the doctrine of comprehensive protection. This has helped to maintain the punitive treatment inherited from earlier periods without taking their rights into consideration.